2022
DOI: 10.3390/foods11203203
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Acrolein in Neurodegenerative Diseases and Its Protective Strategy

Abstract: Neurodegenerative diseases are characterized by a massive loss of specific neurons, which can be fatal. Acrolein, an omnipresent environmental pollutant, is classified as a priority control contaminant by the EPA. Evidence suggests that acrolein is a highly active unsaturated aldehyde related to many nervous system diseases. Therefore, numerous studies have been conducted to identify the function of acrolein in neurodegenerative diseases, such as ischemic stroke, AD, PD, and MS, and its exact regulatory mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 96 publications
0
9
0
Order By: Relevance
“…Acrolein is a highly active unsaturated aldehyde involved in neurodegenerative diseases such as AD as a result of elevating oxidative stress, polyamine metabolism, neuronal damage (Chang et al, 2022) Our results indicated a signi cant increase in acrolein levels in D-gal and ALCL 3 (AD model) compared with control group which may be due to elevated intracellular iron concentration and a depletion of antioxidant enhance ROS levels which consequently induce formation of many secondary products, such as acrolein (Wang et al, 2022).Furthermore, the induction of acrolein in neuronal cells could be related to increase the expression of spermidine/spermine N1-acetyltransferase (SAT1) (Đorđievski et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Acrolein is a highly active unsaturated aldehyde involved in neurodegenerative diseases such as AD as a result of elevating oxidative stress, polyamine metabolism, neuronal damage (Chang et al, 2022) Our results indicated a signi cant increase in acrolein levels in D-gal and ALCL 3 (AD model) compared with control group which may be due to elevated intracellular iron concentration and a depletion of antioxidant enhance ROS levels which consequently induce formation of many secondary products, such as acrolein (Wang et al, 2022).Furthermore, the induction of acrolein in neuronal cells could be related to increase the expression of spermidine/spermine N1-acetyltransferase (SAT1) (Đorđievski et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…They damage the organs mentioned above and ultimately can result in their complete dysfunction, which threatens the health and life of patients [ 68 , 69 ]. Numerous studies indicate a large share of acrolein in the pathogenesis of many diseases related to cardiovascular diseases [ 70 ], neurodegenerative diseases [ 71 ], and chronic obstructive pulmonary disease (COPD) [ 5 ], as well as in the carcinogenesis of various types of cancer [ 9 , 72 ]. Accumulated evidence also clearly indicates the participation of acrolein in the development of diabetic complications, such as DR, DN, and neuronal dysfunction in patients with sugar metabolism disorders [ 4 , 73 , 74 ].…”
Section: Acrolein In the Pathogenesis Of Diabetesmentioning
confidence: 99%
“…Additionally, acrolein can be formed during certain cooking processes, such as frying or grilling, especially when oils and fats are heated to high temperatures ( Stevens and Maier, 2008 ; Kassem et al, 2018 ). Within the body, it can be produced as the end product of lipid peroxidation, threonine degradation, anticancer drug metabolism, and polyamine catabolism ( Chang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%